The Ottoman tanbûr : the long-necked lute of Ottoman art music - Zeeuw, Hans de (Archaeopress Archaeology, 2022)
"Tanbûrs are long-necked lute-like instruments played in the art, Sûfî, and folk musical traditions along the Silk Road and beyond. This book provides a detailed study of the history of the tanbûr, its role in Ottoman music, construction and playing technique. The Ottoman Tanbûr provides a detailed study of the history of this long-necked lute-like instrument, its role in Ottoman music, construction and playing technique. Tanbûrs are played in the art, Sûfî, and folk musical traditions along the Silk Road and beyond. In Turkey, the name tanbûr is mainly used as a name for the long-necked tanbûr of Ottoman art music, the Ottoman tanbûr. The origin and early development of the Ottoman tanbûr is, notwithstanding its importance, still not fully understood due to the absence or scarcity of literary and iconographical sources, while well-preserved Ottoman tanbûrs are rare or non-existent. The book explores the political and cultural-historical conditions that contributed to the development of a distinct Ottoman Art music (Osmanlı san'at mûsîkîsi) in the seventeenth and eighteenth centuries and the central place given to the tanbûr. Thereafter, Ottoman art music and the Ottoman tanbûr suffered from official neglect until the end of the Ottoman Empire in 1918 and even rejection after the establishment of the Republic of Turkey in 1923. This situation changed after the foundation of the first Turkish music conservatory in 1975 at the Istanbul Teknik Üniversitesi (ITÜ). The revival of Ottoman art music since the 1990s resulted in a rehabilitation of Ottoman art music and of the Ottoman tanbûr whose days had seemed to be numbered."--